Does pay raise decrease temporary agency workers' voluntary turnover over time in China? Understanding the moderating role of demographics. Issue 7 (12th April 2021) - Lin, Li; Bai, Yuntao; Mo, Changwei; Liu, Dong; Li, Xiyuan
Abstract: China's continued economic development relies heavily on its vibrant human resources, a large portion of which is accounted for by temporary agency workers (TAWs). However, researchers have yet to investigate the factors that are related to TAWs' retention in China. To address this research void, we take a contingency perspective on the relationship between TAW pay raise and voluntary turnover by examining the moderation effects of demographics on the relationship. Drawing on economic exchange theory and human capital theory, we reason that six identity-related demographic factors (namely hukou status, gender, age, education, tenure and occupation type) may alter the negative relationship between pay raise and voluntary turnover (hereafter referred to as turnover). Probit regression analyses of unbalanced panel data from 1184 TAWs over four years support the moderating effects of five of the six demographics ( hukou, gender, age, education and tenure) on the negative pay raise − turnover link. The findings of this study provide important theoretical and practical insights for understanding TAWs' retention in China.